The Effect of Spraying Boron and Seaweed Extracts (kelpak) on Vegetative Growth Characteristics and Concentration of Some Medically Active Substances for Lemon Grass (Cymbopogon Citratus L.) - Nazar Hasan, Mohammed; ., . (International Journal of Engineering and Technology, 2018)
This study includes the effect of spraying boron and seaweed extracts kelpak in the vegetative growth characteristics and concentration of some medically active substances for lemongrass plant. The experiment used a randomized complete block design with three replications. The Medians treatments have compared using Duncan’s test with multi limits at 5% possibility. The results arrived at can be summed up as follows. Discriminate treatment (B1K1) the highest rate of number of leaves (9.61 leave/plant) and the highest rate in plant height (134.14 cm), compared with comparison transaction ( B0K0 ) it gave the lowest rate for the number of  leaves  and  less  height  of  the plants. While the  treatment  giving  overlap (B2K2) the  highest  moral value  Percentage  of  dry matter for total vegetative  (24.00)  and the  highest  rate  of  percentage of dry matter for total root (33.00) and  the  highest  rate  of  leaves area  (168.08 cm2/leave) and the  highest  total chlorophyll concentration (35.18 SPAD) Compared with the  least in comparison transaction ( B0K0 ) that  gave less rate in percentage of dry matter for total vegetative and root and the  less total chlorophyll concentration. Influenced treatment (B1K1) in the concentrations of the activeA substances to give it the highest concentrations of  Myrcene (3.47 mg/gm) and Citral (28.01 mg/gm) and Limonene (42.72 mg/gm) and Geraniol (38.42 mg/gm) compared  to the  rest of the  other transactions, while the lower concentrations of these in the treatment comparison ( B0K0).